Phytoremediation of Chromium and Copper from Aqueous Solutions Using Hydrilla verticillata - Abdul-Alghaffar , Huda N.; Al-Dhamin, Ahmad S. (Iraqi Journal of Science, 2023)
The current study included testing the ability of plant Hydrilla verticillata (L. F.) on the accumulation of two heavy metals in its tissues, and use the plant in phytoremediation. The plant was exposure to different concentrations of chromium and copper metals (2.5, 5, 10, 15, 20) ppm, for a period of fourteen days, for each solution.The results showed that Hydrilla was more efficient in the removal of chromium, where the amount of the remaining concentration of chromium at the last day of the experiment was (0.20 ± 0.014- 0.66 ± 0.114- 0.99 ± 0.176- 0.79 ± 0.073- 1.80 ± 0.131) ppm, while for copper was (0.33 ± 0.06- 1.13 ± 0.39- 1.66 ± 0.05- 1.96 ± 0.043- 2.33 ± 0.0497) ppm at the last day of the experiment, respectively.